"1) We \\, find \\, f'(x):\\\\ \nf'(x) = -3x^2 + 4x-1; \\\\ \n2) f'(x) = 0 \\\\ \n-3x^2 + 4x - 1 = 0; \\\\ \n3x^2 - 4x +1 = 0; \\\\ \nD = b^2 - 4ac = (-4)^2 - 4*3*1 = 16 - 12 = 4; \\\\ \nx_1 = \\frac{-b - \\sqrt{D}}{2a} = \\frac{4 - 2}{2*3} = \\frac{2}{6} = \\frac{1}{3}; \\\\\nx_2 = \\frac{-b + \\sqrt{D}}{2a} = \\frac{4 + 2}{2*3} = \\frac{6}{6} = 1;"
3)
"4) \\newline\nf(0) = -0^3+2*0^2-0= 0; \\newline\nf(\\frac{1}{3}) = -(\\frac{1}{3})^3 + 2(\\frac{1}{3})^2 - \\frac{1}{3} = -\\frac{4}{27};\\newline\nf(1) = -1^3 +2*1^2-1 = 0; \\newline\nf(2) = -2^3 + 2*2^2 - 2 = -2;\\\\\nmax \\, f=max \\{0; -\\frac{4}{27};-2\\}=0;\\\\\nmin \\,f=min \\{0; -\\frac{4}{27};-2\\}=-2.\\\\"
5) Therefore, the function "f(x) = -x^3 + 2x^2 - x" in the interval "[0,2]" has its own minimum equal to "-2" (the function attains this minimum at the point "x=2") and the function has the maximum equal to 0 (the function attains this maximum at the points "x = 0" and "x=1").
Comments
Leave a comment